2018
DOI: 10.1093/scan/nsy027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intranasal oxytocin on interoceptive accuracy in alcohol users: an attentional mechanism?

Abstract: Interoception, i.e. the perception and appraisal of internal bodily signals, is related to the phenomenon of craving, and is reportedly disrupted in alcohol use disorders. The hormone oxytocin influences afferent transmission of bodily signals and, through its potential modulation of craving, is proposed as a possible treatment for alcohol use disorders. However, oxytocin’s impact on interoception in alcohol users remains unknown. Healthy alcohol users (n = 32) attended two laboratory sessions to perform tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 93 publications
0
26
1
Order By: Relevance
“…However, significant differences in smoking habits were also present, and additionally, participants were undergoing inpatient treatment for addiction (including pharmacological therapies that may affect bodily states) at the point of testing. In contrast, a recent study conducted by Betka et al (2018; smoking status of participants unknown) found that heavy (non-clinical) alcohol consumption was not associated with IS. Together, the findings from these studies suggest that addiction specifically, rather than nonclinical consumption of a substance, is associated with impaired IS.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…However, significant differences in smoking habits were also present, and additionally, participants were undergoing inpatient treatment for addiction (including pharmacological therapies that may affect bodily states) at the point of testing. In contrast, a recent study conducted by Betka et al (2018; smoking status of participants unknown) found that heavy (non-clinical) alcohol consumption was not associated with IS. Together, the findings from these studies suggest that addiction specifically, rather than nonclinical consumption of a substance, is associated with impaired IS.…”
mentioning
confidence: 72%
“…Whilst some previous studies have found correlations between the heartbeat perception tasks (Hart, McGowan, Minati & Critchley, 2013;Knoll & Hodapp, 1992) others have not (Betka et al, 2018;Forkmann et al, 2016;Michal et al, 2014;Schulz, Lass-Hennemann, Sütterlin, Schächinger & Vögele, 2013). The tasks are assumed to measure IS in fairly equivalent ways, but actually require quite distinct psychological processing (Forkmann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that BMI impact neither temporal nor spatial aspect of heartbeat sensations (Brener and Kluvitse 1988;Brener et al 1993;Brener 1992, 2018). However, we predict that individual differences in affective functioning (Anxiety, Depression, Alexithymia) will influence both aspects of heartbeat sensation (Betka et al 2017(Betka et al , 2018Khalsa et al 2018;Paulus and Stein 2010). Finally, we expect that heart rate will impact heartbeat perception -namely, slower heart rate (i.e.…”
Section: Aimsmentioning
confidence: 96%
“…Consequently, research has focused on the objective measurement of interoception, using behavioral tasks through which interoceptive accuracy can be quantified from performance (Garfinkel et al 2015). Most widely, such tasks use the perception cardiac sensations at rest: heartbeats are clear and discrete events, which are easily measurable (Betka et al, 2018) and relevant -the changing strength and timing of heartbeats are signatures of changing physiological arousal that accompany relevant emotions, exercise, injury, or illness. Hence, tests of heartbeat perception tasks dominate, providing a baseline metric of interoceptive sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation